Pharmalink: UiTM- UNHAS 2024 fostering international collaboration in pharmacy education / Akmal Haziq Abdul Basit - Abdul Basit, Akmal Haziq (Faculty of Pharmacy, 2024)
From October 23rd to October 28th, the Faculty of Pharmacy at Universiti Teknologi MARA (UiTM) hosted the PharmaLink program, an international exchange initiative aimed at bridging pharmacy students from Malaysia and Indonesia. Organised by the Society of Pharmacy Students (SOPHYS) at UiTM, the program welcomed students from Universitas Hasanuddin (UNHAS) in Makassar, Indonesia, fostering a shared learning environment and cultivating professional networks in the pharmacy field.